Deep Compactor with a Concrete Mixture Laid in a Form Interaction Process Investigation - Maslov, Alexander; Batsaikhan, Janar; Nesterenko Jr., Mykola; Nesterenko Jr., Tatiana (International Journal of Engineering and Technology, 2018)
Analytically, rational parameters of a vibration machine for internal compaction of concrete mixes are determined and rational modes of vibration exposure by a flat working body on a concrete mix are established.The dynamic system â€œvibration machine - concrete mediumâ€ is investigated, in which the latter is represented as a system with distributed parameters, taking into account the elastic, viscous, inertial and energy properties of the concrete to be compacted. The partial differential equation was compiled describing the change in stresses in a compacted medium depending on the dynamic elastic modulus, dynamic viscosity coefficient, inelastic resistance coefficient and inertia of the medium to be densified as a function of density, relative deformation and texture of the concrete mix. The propagation of visco-elastic-plastic deformation waves in a compacted concrete mix, represented as a half-space, is investigated. As a result of solving the wave equation of oscillations, the regularity of the propagation of viscous-elastic-plastic deformation waves in the half-space of a concrete mixture being compacted is established. The amplitudes of vibrations and stresses arising in the compacted mixture are determined depending on its physico mechanical characteristics. The vibration amplitude of the vibration machine was determined, its rational parameters were established, and rational modes of vibration impact on the compacted concrete mix found in the form of a half-space were found. A vibration machine in the form of a flat vertical plate, in the upper part of which a horizontal vibration exciter is mounted, is proposed. The given dependences allow one to substantiate rational ones depending on the physico mechanical characteristics of the medium being compacted, the thickness and width of the layer being compacted, the angular frequency of the forced oscillations and the amplitude of the disturbing force.Â Â Â